Myth, Forgetfulness and Manipulation of the History of Freemasonry - Ferrer Benimeli, José Antonio (2019)
On the occasion of the 10th Anniversary of the journal REHMLAC+ there was an assesment of the historiographical research conducted in the last 40 years and its scope in the real knowledge of the Masonic phenomenon. In light of the meeting of the International Seminar on the History of Freemasonry, this article presents a synthesis around the myth, the forgoten, and the manipulation of the history of Freemasonry with the objective that one day the true Masonic past will occupy the place that myths and legends about the history of Freemasonry had occupied and approproated until now.